Differences in ambulatory blood pressure profiles between Japanese and Thai patients with hypertension /suspected hypertension. Issue 3 (22nd November 2020) - Tomitani, Naoko; Wanthong, Sirisawat; Roubsanthisuk, Weranuj; Buranakitjaroen, Peera; Hoshide, Satoshi; Kario, Kazuomi
Abstract: Ethnic differences in the profiles of hypertension and cardiovascular risk have been reported between Asians and Westerners. However, blood pressure (BP) profiles and the risk factors for cardiovascular disease might differ even among different Asian populations because of the diversity of cultures, foods, and environments. We retrospectively examined differences in 24‐h BP profiles between 1051 Japanese (mean age, 62.5 ± 12.4 years; medicated hypertension, 75.7%) and 804 Thai (mean age, 56.9 ± 18.5 years; medicated hypertension, 65.6%) by using the Japanese and Thai ambulatory BP monitoring (ABPM) databases, in order to check the BP control status in treated hypertensives and to inform the clinical diagnosis of hypertension. The two populations had similar office systolic BP (SBP) (142.7 ± 20.0 vs 142.3 ± 20.6 mm Hg, p  = .679). However, the Japanese population had higher 24‐hr average and daytime SBP, and the Thai population had higher nighttime SBP even after adjusting for cardiovascular risk factors (all p  < .05). Greater morning BP surge was observed in Japanese (31.2 vs 22.8 mm Hg, p  < .001). Regarding nocturnal BP dipping status, the prevalence of riser status (higher nighttime than daytime SBP) was higher in the Thai population (30.5% vs 10.9%). These findings suggest that a substantial difference in 24‐hr BP profiles exists between even neighboring countries in Asia.